FRI0720 Characteristics of patients with gout treated to sua target that continue to experience flares: data from france, germany, italy, spain, uk and us. (15th June 2017) - Morlock, R; Taylor, DC; Baumgartner, S
Abstract : Background: Gout is a common form of inflammatory arthritis. Treatment guidelines recommend a target serum urate (sUA) ≤6mg/dL. ACR and EULAR treatment guidelines indicate sUA targets may need to be surpassed to achieve treatment benefits in a subset of patient that continue to flare and/or have tophi. Methods: Data were assessed from a survey of physicians about gout disease management. Patient results were confirmed through in-depth chart audits assessing diagnosis, comorbid conditions, disease severity and laboratory assessments. Disease severity was measured using a physician global assessment, flare counts, joint damage and presence of tophi. Type and dose of XOI, length of current treatment, compliance, physician type and patient socio-demographic factors were identified. Descriptive and multivariate statistics were used to describe patients having ≥2 flares per year (excluding treatment-related flares) in patients achieving target sUA ≤6 mg/dL. Results: Overall, 251 rheumatologists and 250 primary care physicians were interviewed and provided data from 2505 patients with gout; 82% were male and the average age was 58 years (SD=12). 1823 (73%) patients were treated with an XOI, of these 813 (44%) had a least one assessment of sUA ≤6 mg/dL over a 12-month period. Of the 813 patients reaching sUA target, 307 (37.8%) reported ≥2 flares in the last year. On average, patients at sUA goal with ≥2 flares had been treated over 38.8 months on their current XOI and patients with ≤1 flare had been treated for 40.7 months. Patients at sUA ≤6 mg/dL treated with an XOI and reporting ≥2 flares a year were more likely to have tophi (32.9% vs. 19.2%; p<0.01), alcoholism (22.8 vs. 10.7; p<0.01), CVD (24.8 vs. 17.6%; p=0.014), depression (14.3 vs. 9.3; p=0.027), and diabetes mellitus (23.8 vs. 16.8; p=0.015) compared to patients with ≤1 flare a year. A backward stepwise multivariate model predicting patients classified as controlled (sUA ≤6 mg/dL) and continuing to flare (≥2 flares in the last year) found the physician-reported and chart-documented comorbidities of chronic kidney disease (OR 1.9; p<0.01), alcoholism (OR 2.4; p<0.01), diabetes mellitus (OR 1.5; p<0.05), and have tophi (1.7; p<0.01) to be associated with having higher flare rates despite achieving sUA ≤6 mg/dL. There was no difference by the type of XOI or physician. Conclusions: Of the patients achieving target sUA level of ≤6 mg/dL, 62% have ≤1 flare; however, over a third reported ≥2 in a 12-month period. Patients with multiple flares were more likely to have higher urate burden in the form of tophi, chronic kidney disease, alcoholism, and diabetes mellitus comorbid conditions. Frequent flares and greater tophaceous burden may require treating more aggressively to an sUA level of 5 mg/dL or lower as recommended by treatment guidelines. Acknowledgements: This study was funded by Ironwood Pharmaceuticals. Disclosure of Interest: R. Morlock Consultant for: Ironwood Pharmaceuticals, D. Taylor Employee of: Ironwood Pharmaceuticals, S. Baumgartner Consultant for: Ironwood Pharmaceuticals